Bigger or better: The relative benefits of protected area network expansion and enforcement for the conservation of an exploited species. Issue 3 (10th January 2018) - Kuempel, Caitlin D.; Adams, Vanessa M.; Possingham, Hugh P.; Bode, Michael
Abstract: The global portfolio of protected areas is growing rapidly, despite widely recognized shortfalls in management effectiveness. Pressure to meet area‐coverage and management effectiveness objectives makes it essential to determine how limited conservation funds should be allocated between expanding protected area networks and better enforcing existing reserves. We formally explore this question for the particular case of an exploited species in a partially protected system, using a general model linking protection, enforcement and legal/illegal resource extraction. We show that, on average, funds should be disproportionately invested in enforcement rather than expansion. Further, expansion alone, without additional enforcement, can actually reduce conservation outcomes. To help guide future decisions, we calculate the optimal allocation of resources between these two actions given any current level of enforcement and protected area coverage. In most cases, simultaneously investing in expansion and enforcement is the optimal decision. However, in places with low enforcement and high protection, protected area contraction, or strategically concentrating enforcement effort, produces the greatest benefits.